Productive Utilisation of Non-arable Lands through Watershed Management in the Semi-arid Regions of South India - Rama Mohan Rao, M. S.; Padmaiah, M.; Raizad, A.; Ayyappa, B. (Indian Forester, 1994)
Multiple benefits which could be derived over a short period of time, after adopting various practices of floriculture, horticulture and tree plantations, on non-arable lands, in the semi-arid zones of Southern India are presented in this paper. Jasmine (Jasminium sambac Ait.) cultivation along river bank, is a profit-able activity, while application of DAP on grasses established over barren hill slopes, significantly increased dry matter yields. Tree plantations carried out along canal banks were better than those planted on hills, although tree survival on hill slopes was 40% and satisfactory.